Mentoring for the Preparation of Sustainability Development Goals (SDG's) Report in LAZISMU East Java - Sigit Hermawan; Eny Maryati; Irwan Alnarus Kautsar; Prasetyo Utomo; Sultan Akhsanuddin Adillah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Amil zakat institutions in Indonesia are obliged to contribute to solving national and international problems such as achieving the Sustainability Development Goals (SDGs). The purpose of this community service activity is to socialize, compile, and assist in SDGs reporting at Amil Zakat Infaq and Shadaqah Muhammadiyah (Lazismu) East Java. The target partners are 12 people consisting of the chairman, secretary, deputy chairman of the management board, financial manager, fundraising manager, distribution manager and staff. The method of implementation in this community service is socialization, preparation, and assistance in SDGs reporting by the community services team. The results of the activity are the socialization of the 17 SDG's goals and their indicators that have been carried out by the community service team. Furthermore, the preparation of the SDG's report was carried out by the distribution section of Lazismu Jatim with assistance from the community service team. The result is that the distribution of funds in 2023 by Lazismu East Java contributes to SDG's goal number 1 without poverty by 3.44%; number 2 without hunger by 43.82%; number 3 healthy and prosperous life by 0.47%; number 4 quality education by 0.68%; number 6 clean water and proper sanitation by 0.39%; number 7 clean and affordable energy by 0.1%. Furthermore, number 8 decent work and economic growth by 1.74%; number 13 handling climate change by 8.65%; number 14 marine ecosystems by 0.03%; number 16 peace, justice and institutions by 34.5%; number 17 partnerships to achieve goals by 6.18%.  Another result is an increase in the knowledge and skills of the partner team to compile the SDG's report which is indicated by the results of the pre-test and post-test that there are changes with better scores